The effects of folic acid on RNA m6A methylation in hippocampus as well as learning and memory ability of rats with acute lead exposure. (January 2021) - Li, Ning; Zhang, Di; Cao, Shuai; Qiao, Mingwu; Zhang, Pingan; Zhao, Qiuyan; Shen, Yue; Huang, Xianqing; Song, Lianjun
Graphical abstract: Highlights: Lead exposure increased the level of Fat mass and obesity-associated protein expression in brain tissue. Lead exposure resulted in decreased N6- methyladenosine levels, learning and memory ability. The level of m6A after the intervention of folic acid, and the obvious improvement in learning and memory ability. Abstract: The heavy metal lead in the environment is a neurotoxin with very strong biological toxicity which can cause serious damage to the learning and memory ability of humans and animals, folic acid can be involved in biological process to prevent impaired learning and memory. however, the specific mechanism is not clear. Herein, in order to explore whether folic acid has a protective effect on learning ousing on the M6A of FTO/METTL3 pathway control and learning and memory ability by lead exposure. Forty 6-week-old male rats were randomly divided into four groups, which drinking water freely model to establish folic acid (0.4 mg/ kg ·bw/day) intervention model of acute lead (0.2% lead acetate solution) exposure, and the determination of lead in hippocampus and Serum by GFAAP and the expression of FTO and METTL3 protein was detected by immunofluorescence assay, the methylation level of m6A in hippocampus was detected by EpiQuik TM m6A RNA methylation quantitative. A Morris water maze was used to test the spatial learning and memory ability of animals by positioning navigation experiment and space exploration experiment. Result display: Comparing to the control group, in the hippocampus, the expression of FTO in the lead exposure group was significantly increased ( P  < 0.05), while METTL3 and M6A were significantly reduced in the lead exposure group ( P  < 0.05). The ability of learning and memory in folic acid group was significantly high than that in lead exposure group ( P  < 0.01). Our data showed that folic acid can effectively protect the body's ability of learning and memory by enhancing the mechanism of RNA m6A.